2 UMP Innovation Project named 2021 IIC champions - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 9 June 2022 - Two innovation projects produced by a group of Universiti Malaysia Pahang (UMP) staff, namely Buku Si Comel or Buku Imunisasi Baby Digital (Buku Pink) and the AgroTrack Project took first place and won a gold medal in the International Innovation Competition (IIC) 2022 took place at Temerloh Community College recently.